Financial constraints and trade credit: Evidence from Ethiopian firms - Dereje Getachew Regasa; Bekele Abraham (Cogent Economics & Finance, 2022)
There is an extensive literature that links firms' access to formal financial services and trade credit. This is more relevant for firms operating in financially less developed countries. These firms could potentially face a binding bank loan constraint due to the distortions related to information asymmetry and moral hazard. Against this backcloth, this paper will explore the relationship between trade credit and financial constraints for Ethiopian firms. The main objective of this study is to explore the relationship between trade credit practice and financial constraints for Ethiopian manufacturing and service firms. We exploit the repeated cross-sectional data of 2011 and 2015 made available by the World Bank's Ethiopian Enterprise Survey. To address the endogeneity problem between financial constraint and trade credit, the paper employs an instrumental variable (IV) approach. We find a negative relationship between financial constraint and trade credit use. In particular, financially constrained firms have a trade credit use which is about 10 to 18 percentage points lower than unconstrained firms, suggesting that bank credit constrained firms are also trade credit constrained. One policy implication is that addressing constraints in formal financing is more likely to increase the availability of alternative forms of finance such as trade credit.
Keywords: 330; trade credit; Ethiopia; financial constraint; control function